2008
DOI: 10.1021/jp804846n
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR Study on the Self-Association of Quinacridone Derivatives in Solution

Abstract: The pi-stacking structures and self-association thermodynamics of N, N'-di(n-alkyl) quinacridone derivatives (n-alkyl QAs) with various substituents on the side aromatic rings and different length of n-alkyl chains are investigated in organic solvents by (1)H NMR spectroscopy. The stacking geometries are built based on both the magnitudes and directions of peak shifts with concentration and solvent polarity. The intermolecular interaction between nitrogen atoms and oxygen atoms dominates the general geometrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…The least fractions of the parallel displaced geometries were found in DX-QA-C 4 dimers. 49 The comparison between the interaction energies of the two types of configurations gives similar conclusion. The data in Table 1 show that the energy difference between PD and r-APD/APD configurations of DF-QA-C 1 dimer is much larger than those of other dimers.…”
Section: Comparison With Nmr Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…The least fractions of the parallel displaced geometries were found in DX-QA-C 4 dimers. 49 The comparison between the interaction energies of the two types of configurations gives similar conclusion. The data in Table 1 show that the energy difference between PD and r-APD/APD configurations of DF-QA-C 1 dimer is much larger than those of other dimers.…”
Section: Comparison With Nmr Resultssupporting
confidence: 57%
“…The theoretically predicted geometries of the QA dimers are in good agreement with the NMR results of N,N 0 -di(n-alkyl) quinacridone derivatives. 49 In the NMR study of these quinacridone derivatives, we observed two types of dimeric geometries coexisting in solution, corresponding to the parallel displaced and antiparallel displaced configurations. Theoretical calculation even predicted correct rotation direction of one monomer relative to the partner in the r-APD configuration of DM-QA-C 1 dimer (corresponding to D t Bu-QA-C n in ref.…”
Section: Comparison With Nmr Resultsmentioning
confidence: 95%
See 3 more Smart Citations